2022
DOI: 10.3390/horticulturae8040307
|View full text |Cite
|
Sign up to set email alerts
|

Root-Zone Amendments of Biochar-Based Fertilizers: Yield Increases of White Cabbage in Temperate Climate

Abstract: The use of biochar is an important tool to improve soil fertility, reduce the negative environmental impacts of agriculture, and build up terrestrial carbon sinks. However, crop yield increases by biochar amendment were not shown consistently for fertile soils under temperate climate. Recent studies show that biochar is more likely to increase crop yields when applied in combination with nutrients to prepare biochar-based fertilizers. Here, we focused on the root-zone amendment of biochar combined with mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Plants grown in a highly nutrient-rich environment usually develop lower root mass but higher leaf and stem mass fractions, promoting light interception and photosynthesis [41]. Moreover, Grafmüller et al [42] suggested that adding nutrient-enhanced biochar in the root area may act as a hotspot for the plant, which requires fewer fine roots for nutrient supply. Below-ground biomass was inversely proportional to compost dilution.…”
Section: Plant Developmentmentioning
confidence: 99%
“…Plants grown in a highly nutrient-rich environment usually develop lower root mass but higher leaf and stem mass fractions, promoting light interception and photosynthesis [41]. Moreover, Grafmüller et al [42] suggested that adding nutrient-enhanced biochar in the root area may act as a hotspot for the plant, which requires fewer fine roots for nutrient supply. Below-ground biomass was inversely proportional to compost dilution.…”
Section: Plant Developmentmentioning
confidence: 99%
“…Five replicate pots per treatment were either prepared for cultivation with or without leaching events, the latter including a non-fertilized control (CTRL-0) to test for leaching of native soil nutrients and mineralized N (Table 1 ). A control group without fertilizer/biochar application and without leaching events was not conducted as a pre-trial showed that no cabbage head development could be expected 13 . Five additional pots for NPK, gBBF, and B + NPK without leaching were set up for repeated sampling to measure soil N speciation and urease activity over time (cf.…”
Section: Methodsmentioning
confidence: 99%
“…The biochar-based efficient use of fertilizer can avoid the manufacturing fraction of fertilizers and associated GHG emissions [79]. Biochar-based fertilizers can increase crop productivity significantly and further increase crop productivity in soils which are not responsive to common fertilizers (Figure 3A) [80].…”
Section: Biocharmentioning
confidence: 99%